Phosphorylated Y14 condensates as a scaffold for DNA double-strand break repair - Chun-Hao Su; Tzu-Wei Chuang; Hsin-Hong Yeh; Chiu-Lun Shen; Pei-Yu Hung; Ying Li; Woan-Yuh Tarn (iScience, 2025)
Summary: Various DNA damage response factors form biomolecular condensates at DNA lesions. Targeting phase separation in DNA repair factor assemblies may provide a potential anticancer strategy. An RNA-binding protein, Y14/RBM8A, facilitates the repair of DNA double-strand breaks (DSBs) via its RNA-mediated interaction with non-homologous end joining (NHEJ) factors. HaloTag-Y14 fusion is distributed to laser-induced DNA damage sites in an RNA-dependent manner. Serine/arginine (SR) protein kinase 1-mediated phosphorylation of Y14 was also crucial for its localization at DNA lesions and function in DSB repair. Magnesium promoted liquid-liquid phase separation of phosphorylated Y14 in vitro. Ku70/80 could partition into phosphorylated Y14 condensates. Chelation of divalent cations abolished Y14 localization and subsequent recruitment of NHEJ factors at DNA damage sites. Inhibition of Y14 phosphorylation interfered with Ku70/80 recruitment and increased the sensitivity of cancer cells to DNA damage. This study reinforces that manipulating DNA repair foci can improve the efficacy of anticancer agents.